2018
DOI: 10.15406/apar.2018.08.00350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic and chemical sources of nitrogen and seedling age at transplant on growth and yield of Kohlrabi

Abstract: The research was carried out in the fields of HASERA Agriculture Research and Training Center, Nepal during the winter of 2017/18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(20 reference statements)
2
3
0
Order By: Relevance
“…On the other hand the minimum number of leaves per plant (13.72) was observed from S 1 (20 days age of seedling) treatment. Similar result was also found by [10] who reported that 28 days seedling increases the number of leaves per plant.…”
Section: Number Of Leaves Per Plantsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand the minimum number of leaves per plant (13.72) was observed from S 1 (20 days age of seedling) treatment. Similar result was also found by [10] who reported that 28 days seedling increases the number of leaves per plant.…”
Section: Number Of Leaves Per Plantsupporting
confidence: 89%
“…The maximum fresh weight of knob with leaves per plant (218.07 g) was revealed from S 2 (25 days age of seedling) treatment while the minimum fresh weight of knob with leaves per plant (191.24 g) was observed from S 1 (20 days age of seedling) treatment (Table 3). Dhital et al [10] observed the similar trends of result and reported that knob weight and circumference was significantly higher in 28days seedling than 14days seedling.…”
Section: Fresh Weight Of Knob With Leaves Per Plantsupporting
confidence: 56%
See 1 more Smart Citation
“…The increased growth parameters attributed to beneficial effect of poultry manure has been reported by [16] and [17] in radish, [18] in carrot and [19] in beetroot. [27,28] and [26] reported that the effect of application of poultry manures on growth of radish (Raphanus sativus L.) and pakchoi (Brassica chinensis L.). The increased growth parameters attributed to beneficial effect of poultry manure has been reported by [16] and [17] in radish, [18] in carrot and [19] in beetroot.…”
Section: Leaf Length (Cm)mentioning
confidence: 99%
“…Whereas, the good-aged seedlings increase the area of leaves, the yield, the number of fruits and the weight of the fruits [12], therefore, the cultivation of seedlings at the appropriate and optimal age is of paramount importance, as its yield is positively reflected on the yield quantitatively. [13] explained when conducting a study in Nepal during the winter of 2017/2018 to show the effect of the age of seedlings (14 days, 28 days) kohlrabi seedlings at 14 days old had the highest values for growth characteristics, and those at 28 days old had the highest values for yield characteristics. The success of crops depends upon supplement contribution and development.…”
Section: Introductionmentioning
confidence: 99%